2021
DOI: 10.1039/d1qi00347j
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the chemical composition on the structural, thermodynamic, and mechanical properties of all-inorganic halide perovskites

Abstract: Organic-inorganic hybrid halide perovskites are widely used in optoelectronic devices such as solar cells and light emitting devices. Pursuing solutions to a key problem of instability in most used MAPbI3,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
0
8
0
1
Order By: Relevance
“…La publicación más relevante de este autor en términos de número de citas, se publicó en 2011 y fue un estudio sobre un nuevo material de banda intermedia para un mejor aprovechamiento del espectro solar (Wahnón et al, 2011). Este autor tiene una fuerte coautoría con Palacios, P. (Sánchez-Palencia et al, 2022), (Sánchez-Palencia et al, 2021, (Sánchez-Palencia et al, 2020), y con Aguilera, I. (Das et al, 2022).…”
Section: Instituciónunclassified
“…La publicación más relevante de este autor en términos de número de citas, se publicó en 2011 y fue un estudio sobre un nuevo material de banda intermedia para un mejor aprovechamiento del espectro solar (Wahnón et al, 2011). Este autor tiene una fuerte coautoría con Palacios, P. (Sánchez-Palencia et al, 2022), (Sánchez-Palencia et al, 2021, (Sánchez-Palencia et al, 2020), y con Aguilera, I. (Das et al, 2022).…”
Section: Instituciónunclassified
“…1,2 In order to address the above issues, new solar cells such as semiconductor thin-film cells, organic perovskite cells, and ferroelectric photovoltaic devices have received widespread attention in recent years. [3][4][5][6][7][8] Theoretical calculations showed that photovoltaic devices based on ferroelectric materials might break through the Shockley-Queisser limit of traditional silicon-based photovoltaic cells, thus becoming a research hotspot in the field of new photovoltaic cells. 1,9 Nevertheless, traditional ferroelectric materials (LiNbO 3 , BaTiO 3 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the elastic properties of materials are of vital importance since they not only determine the long-term reliability and endurance in service but also regulate the manufacturing and processing [ 33 , 34 ]. However, very little attention has been paid to the understanding of the elastic properties of LD-MHPs [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%